(untitled) (Research, Society and Development, 2022)
This study aimed to elicit students’ perspectives on learning English online at Quevedo Technical University. The researchers examined their modality preference, technological issues, and the positives and negatives of this mode. Also, explored students’ assumptions regarding best knowledge and retention. The researchers employed a quantitative and qualitative methodology. They distributed a questionnaire to collect data among students of the seventh-level of English course. The participants were asked to fill out a 5-point Likert scale questionnaire and four open-ended questions to support students’ answers in the first part. The questionnaire also included an additional unnumbed item to know the learners´ perception about what mode retains the most and best knowledge. The findings showed a preference for online learning besides technical problems such as the internet. Learners find now more positive things to learn from home remotely than negative ones. Saving time, and money, reviewing classes on their own time, and flexibility are the most positive aspects of online learning.